Double burden or Newfound freedom? Women’s empowerment amid large-scale male labor migration from rural Tajikistan - Lambrecht, Isabel B.; Mardonova Tolibkhonovna, Mohru; Pechtl, Sarah; Teirlinck, Charlotte (International Food Policy Research Institute, 2025)
Labor migration is generally motivated by the prospect of higher earnings abroad, and many migrants support their left-behind household members through remittances. Migrants’ long-term absence from home may, however, also affect intra-household dynamics among those remaining behind. Relying on primary qualitative data as well as quantitative data from 938 married women, we analyze empowerment impacts of migration on women in rural southern Tajikistan. Tajikistan is one of the most remittance-dependent countries in the world. A large share of young men migrates internationally, leaving behind – and often supporting – a multi-generational household. Yet, strong social norms limit the decision-making power and mobility of women, particularly of young women. Whereas senior women report noticeable differences when their spouses migrate, this is far less so for young women who live with their parents-in-law. Our study demonstrates that accounting for a respondent’s position within the household is key to understanding empowerment outcomes of its members.